Right Ventricular Imaging and Computer Simulation for Electromechanical Substrate Characterization in Arrhythmogenic Right Ventricular Cardiomyopathy - Mast, Thomas P; Teske, Arco J; Walmsley, John; van der Heijden, Jeroen F; van Es, René; Prinzen, Frits W; Delhaas, Tammo; van Veen, Toon A; Loh, Peter; Doevendans, Pieter A; Cramer, Maarten J; Lumens, Joost (Journal of the American College of Cardiology, 2016)
Previous studies suggested that electrical abnormalities precede overt structural disease in arrhythmogenic right ventricular cardiomyopathy (ARVC). Abnormal RV deformation has been reported in early ARVC without structural abnormalities. The pathophysiological mechanisms underlying these abnormalities remain unknown. The authors used imaging and computer simulation to differentiate electrical from mechanical tissue substrates among ARVC clinical stages. ARVC desmosomal mutation carriers (n = 84) were evaluated by electrocardiography (ECG), Holter monitoring, late-enhancement cardiac magnetic resonance imaging, and echocardiographic RV deformation imaging. Subjects were categorized based on the presence of 2010 International Task Force criteria: 1) subclinical stage (n = 21); 2) electrical stage (n = 15); and 3) structural stage (n = 48). Late enhancement was not present in any subclinical or electrical stage subjects. Three distinctive characteristic RV longitudinal deformation patterns were identified: type I: normal deformation (n = 12); type II: delayed onset of shortening, reduced systolic peak strain, and mild post-systolic shortening (n = 35); and type III: systolic stretching with large post-systolic shortening (n = 37). A majority (69%) of structural staged mutation carriers were type III, whereas a large proportion of both electrical and subclinical stage subjects (67% and 48%, respectively) were type II. Computer simulations demonstrated that the type II pattern can be explained by a combination of reduced contractility and mildly increased passive myocardial stiffness. This evolved into type III by aggravating both mechanical substrates. Electrical activation delay alone explained none of the patterns. Different ARVC stages were characterized by distinct RV deformation patterns, all of which could be reproduced by simulating different degrees of mechanical substrates. Subclinical and electrical staged ARVC subjects already showed signs of local mechanical abnormalities. Our novel approach could lead to earlier disease detection and, thereby, influence current definitions of electrical and subclinical ARVC stages.